Dietary metabolome profiles of a Healthy Australian Diet and a Typical Australian Diet: protocol for a randomised cross-over feeding study in Australian adults - Clare Collins; Lisa Wood; Tracy Burrows; Jessica Jayne Anne Ferguson; Erin Clarke; Jordan Stanford (BMJ Open, 2023)
Introduction Traditional dietary assessment methods such as 24-hour recalls and food frequency questionnaires rely on self-reported data and are prone to error, bias and inaccuracy. Identification of dietary metabolites associated with different dietary patterns can provide objective markers of whole diet patterns that account for metabolism and individual responses to dietary interventions. Additionally, few studies have investigated country-specific healthy and unhealthy dietary patterns using metabolomics. Therefore, the current study aims to identify urinary and plasma metabolites that characterise a ‘healthy’ (aligned with current national dietary guidelines) and an ‘unhealthy’ dietary pattern (Typical Australian Diet) in Australian adults.Methods and analysis The Diet Quality Feeding Study (DQFS) is an 8-week cross-over feeding study that will recruit 40 healthy adults from the Hunter region (NSW, Australia). Data collected includes biospecimens (whole blood, urine, stool) for quantification of dietary metabolite biomarkers; questionnaires (medical history/demographic, physical activity, quality of life); physical measures (anthropometry, body composition, waist circumference, blood pressure, arterial pressure); skin carotenoids and dietary intake (24-hour recalls, food frequency questionnaire). Participants will attend the research facility every 2 weeks (end of the run-in, each diet intervention and washout period) for collection of physical measures. All food will be provided to participants for each dietary intervention period, and participants will return to their usual diet during the run-in and washout periods. Targeted and untargeted metabolomics using liquid chromatography-mass spectrometry and/or proton nuclear magnetic resonance (1H-NMR) spectroscopy will be used to identify metabolites in biospecimens associated with dietary intake.Ethics and dissemination This study is approved by the Hunter New England Human Research Ethics Committee (HNEHREC; 2022/ETH01649) and the University of Newcastle’s Human Research Ethics Committee (HREC; H-2022-0330). Findings will be disseminated to study participants, funding bodies supporting the DQFS, peer-review publications and presented at scientific conferences within the field of research.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12622001321730).